Early Rise of Serum hCG in Gestational Diabetes Mellitus Women With Live Birth Through In Vitro Fertilization Procedure - Wu, Wei; Zhang, Li-Feng; Li, Yi-Ting; Hu, Tian-Xiao; Chen, Dan-Qing; Tian, Yong-Hong (Frontiers in Endocrinology, 2022)
Gestational diabetes mellitus (GDM) is one of the most common medical complications of pregnancy. The characteristics of early hCG concentration and the rise pattern in patients with GDM after IVF is unknown. We performed a retrospective cohort analysis of eligible viable pregnancies achieved through IVF in our hospital between October 2015 to June 2020. The characteristics of initial hCG concentration and the rise pattern in patients with GDM after IVF and the difference between those of normoglycemic pregnant women were explored. Using random effects models, the preferred pattern to describe the rise of log hCG was quadratic. When the gestational age was within 39 days，the linear model can also adequately characterize the profile and the average slope was 0.173, yielding a predicted increase of 1.55 (55% increase) in 1 day and 3.11 (211%) in 2 days. Absolute hCG values, but not the rate of rise, were significantly higher for double embryos transfer cases and twin pregnancy. Curves of hCG rise derived from GDM group and non GDM group do not differ substantially. In the final model, the hCG values on day-14 and day-16 post oocyte retrieval in GDM group were lower than those in non GDM group with the exception for twin pregnancy. Proportion of patients with low initial hCG values (16 days post oocyte retrieval <100 mIU/mL) was more common in GDM group (5% vs 2.09%)，but there was no statistical significance. The early hCG rise of pregnancy women after IVF, whether GDM or non-GDM ones, could be characterized by quadratic as well as linear model. In addition, the initial hCG values in non GDM group were significantly higher than those in GDM group with exceptions for twin pregnancy. The low hCG value in early pregnancy might be a clue and help for the prediction of GDM in the thereafter gestation.